Students’ Perceptions of the Faculty of Teacher Training and Education (FTIK) IAIN Kerinci on the Effectiveness of Online Lectures during the Covid Pandemic 2019 - Rini Syevyilni Wisda; Yelni Erniyati; Pristian Hadi Putra (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2022)
Abstract: This research was conducted to find out how students perceive the effectiveness of implementing online education during the corona virus outbreak, and to find out what factors are inhibiting and supporting the implementation of online learning during the pandemic. The research method uses quantitative methods, through descriptive surveys. Data collection techniques with questionnaires, interview respondents in this study amounted to 350 students. The results of this study show. Student perceptions of online learning during the pandemic showed that 24.7% of students were satisfied with the implementation of online learning and 75.3% of students expressed dissatisfaction with the implementation of online learning. Student perceptions about the application used zoom meeting 27.4%. the use of the google classroom application is 13%, the etmodo application is 8% and the use of other applications is 7.3%. Students' perceptions about the affordability of access 52.8% can access learning materials anywhere and anytime, and 47.2% say it is difficult to access learning materials. Student perceptions of online learning as independent learning 53.6% said they were satisfied and 46.4% said they were not satisfied. Student perceptions of online learning communication and equity 57.5% said they were satisfied and 42.5% said they were not satisfied. Factors supporting the implementation of online learning are internet quota assistance from the center, flexibility in accessing material (information), developing applications or learning ethnology. The inhibiting factors are increasing costs, uneven network, no variety of methods, and no 2-way communicationKeywords: Perception, Effectiveness, Online learning